Gambaran Castelli’s Risk Index-1 pada Pasien Sindrom Koroner Akut di RSUP Dr. M. Djamil Padang - Eka Musmita Sabebegen; Rismawati Yaswir; Efrida Efrida (Fakultas Kedokteran, Universitas Andalas, 2021)
Atherogenic dyslipidemia is one of the risk factors for the acute coronary syndrome (ACS). Castelli's risk index-1 (CRI-1) is one of which risk markers for ACS. Castelli's risk index-1 is the ratio of total cholesterol and HDL cholesterol. The test is cheap and easy to do in the hospital setting. Objectives: To described CRI-1 in ACS patients in Dr. M. Djamil Padang Hospital. Methods: This descriptive study was carried out in the central laboratory and the CardioVascular Care Unit (CVCU) of Dr. M. Djamil Hospital Padang from September 2017 to September 2018. The population was all ACS patients who have been diagnosed by the clinician. The samples were part of the population that meet the inclusion and exclusion criteria. Colorimetric enzymatic method using automated clinical chemistry used to measure total cholesterol and HDL cholesterol. Results: This study used CRI-1> 4. Data were presented descriptively in a frequency distribution table. Seventy ACS patients were consisting of 50 (71.43%) males and 20 (28.57%) females, with a median age of 60.1 (8.93) years old. The median total cholesterol and HDL cholesterol levels were 178.66 (46.84) mg / dL respectively and 35.71 (10.86) mg / dL. CRI-1 mean is 5.43 (2.27). 81.43% CRI-1 subject results were more than four. Conclusion: The low levels of HDL cholesterol and within normal median total cholesterol level made CRI-1 value increased.Keywords: Acute coronary syndrome, Castelli’s risk index-1